Treated water and peruvian legislation - Raffo Lecca, Eduardo (2013)
The article reviews the issue of water, a renewable natural resource, but unevenly distributed, which has become a rare commodity for some populations. The access to clean water is essential to health, one of the basic human rights and a component of effective policies for the protection of health (WHO, 2006), both in Peru and the world.